2020
DOI: 10.1053/j.jrn.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Hemoglobin Levels With Health-Related Quality of Life, Physical Activity, and Clinical Outcomes in Persons With Stage 3-5 Nondialysis CKD

Abstract: , MS, † and on behalf of CKDopps Investigators* Objective: Conflicting findings and knowledge gaps exist regarding links between anemia, physical activity, health-related quality of life (HRQOL), chronic kidney disease (CKD) progression, and mortality in moderate-to-advanced CKD. Using the CKD Outcomes and Practice Patterns Study, we report associations of hemoglobin (Hgb) with HRQOL and physical activity, and associations of Hgb and physical activity with CKD progression and mortality in stage 3-5 nondialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 37 publications
2
47
3
Order By: Relevance
“…From the data analysis, the hemoglobin level was not correlated with physical activity level (p=1.000). This finding differs from the previous studies [13,33]. Hoshino et al also found declining physical activity level decreased proportionally with lower Hb levels between 10.5 g/ dL and 13 g/dL [13].…”
Section: Physical Activitycontrasting
confidence: 83%
See 2 more Smart Citations
“…From the data analysis, the hemoglobin level was not correlated with physical activity level (p=1.000). This finding differs from the previous studies [13,33]. Hoshino et al also found declining physical activity level decreased proportionally with lower Hb levels between 10.5 g/ dL and 13 g/dL [13].…”
Section: Physical Activitycontrasting
confidence: 83%
“…This finding differed from Hoshino et al and Finkelstein et al studies which found that hemoglobin levels >12 g/dL were associated with a higher quality of life comparing to lower hemoglobin levels [13,27]. This difference might be caused by different studies' subjects.…”
Section: Quality Of Lifecontrasting
confidence: 77%
See 1 more Smart Citation
“…Anemia has been consistently associated with poor outcomes in patients with ND-CKD. In fact, recent reports from the Chronic Kidney Disease Outcomes and Practice Patterns Study (CKDopps) (9) showed a negative association of lower Hb with CKD progression and all-cause mortality (10). Indeed, in an analysis of four community-based longitudinal studies, anemia was associated with a 51% increase in the composite of myocardial infarction, stroke, and all-cause mortality (11).…”
Section: Anemia In Nd-ckd: Common and Harmfulmentioning
confidence: 99%
“…In an analysis of patients with ND-CKD in The Netherlands, individuals with Hb,11 g/dl had considerably worse HRQoL for both physical and mental components of the Short-Form 36 (SF-36) than those with Hb above 11 g/dl (13). An analysis of data from 2121 individuals included in the CKDopps provided evidence that Hb had a positive monotonic association with HRQoL even extending to .12 g/dl (10).…”
Section: Anemia In Nd-ckd: Common and Harmfulmentioning
confidence: 99%